RESEARCHING TERRORISM IN SOUTH AFRICA: MORE QUESTIONS THAN ANSWERS - Solomon, Hussein (Scientia Militaria - South African Journal of Military Studies, 2012)
South Africa confronts a tangible terror threat in the form of some terrorists targeting the country itself, whilst others find it useful as an operational base to strike at targets elsewhere. Far from attempting to provide a comprehensive study of this phenomenon, this article aims to point out the pitfalls of researching terrorism in the South African context. This largely stems from mixed signals emanating from the South African government as well as the reluctance on the part of Pretoria’s securocrats to answer questions pertaining to terrorism. Two reasons are advanced to explain this: incompetence and political correctness. Such mixed signals, it is argued, also confuse the security apparatus of the state itself. This, in turn, serves to frustrate counter-terror efforts.